Biological behaviour and clinical outcome in 42 cats with sarcoids (cutaneous fibropapillomas). (4th May 2020) - Wood, Christopher J.; Selmic, Laura E.; Schlag, Ariel N.; Bacmeister, Cynthia; Séguin, Bernard; Culp, William T. N.; Ayres, Sara A.; Sumner, Julia P.; Byer, Brittney; Mayer, Ursula K.; Liptak, Julius M.
Abstract: Feline sarcoids (or cutaneous fibropapillomas) are rare dermal neoplasms. There are currently no reported statistics concerning their clinical behaviour. Our objective with this retrospective, multi‐institutional study was to describe the clinical presentation and biological behaviour of sarcoids in cats and to determine the oncologic outcome following surgical resection. Medical records from a laboratory database and six contributing institutions were searched to identify cats with histologically confirmed sarcoids. Forty‐two cats were included in the study. The majority of sarcoids occurred on the face, particularly rostral locations such as the lips and nasal planum. Complete and incomplete histologic excision was achieved in 18 and 21 cats, respectively. The overall local recurrence rate was 40.5%. Complete histologic excision was associated with a significantly lower local recurrence rate (11.1%) and longer disease‐free interval (not reached) compared with cats with incompletely excised sarcoids (66.7% and 250 days, respectively). The 1‐ and 2‐year local recurrence rates were 0% and 7%, respectively, for cats with complete histologic excision, and 67% at both time intervals for cats with incomplete histologic excision. Five of the cats (83.3%) treated with curative‐intent surgical revision following local tumour recurrence had no further local recurrence. All cats that died secondary to tumour‐related causes had initial incomplete histologic excision and were euthanized because of local recurrence. Wide surgical resection of feline sarcoids is recommended to achieve complete histologic excision, local tumour control and a potential cure. For cats with incomplete histologic excision or local tumour recurrence, repeat surgical resection is recommended.